The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1103/physrevc.90.054611
|View full text |Cite
|
Sign up to set email alerts
|

Ternary-fission mass distribution ofCf252: A level-density approach

Abstract: We study here the ternary-fission mass distribution of the 252 Cf nucleus for a fixed third fragment 48 Ca using the level-density approach within the framework of statistical theory. For the evaluation of nuclear level densities, the single-particle energies of the finite-range droplet model are used. Our results for temperatures T = 1 and 2 MeV reproduce qualitatively the experimental expectation of ternary fragmentation of 132 Sn + 72 Ni + 48 Ca. In addition, different possible ternary-fission modes are hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
5
12
0
Order By: Relevance
“…The possible binary fragments of the considered nucleus is obtained by equating the charge to mass ratio of the parent nucleus to the fission fragments as [17]:…”
Section: Formalismmentioning
confidence: 99%
“…The possible binary fragments of the considered nucleus is obtained by equating the charge to mass ratio of the parent nucleus to the fission fragments as [17]:…”
Section: Formalismmentioning
confidence: 99%
“…Theoretically, Manimaran and Balasubramaniam found that the fragments 34,36,38 Si, 46,48 Ar and 48,50 Ca associated fragmentations are the most favoured for the ternary fission of 252 Cf within the three-cluster model [30]. In addition, the combination Sn + Ni + Ca is the most favourable from the statistical studies [34] and also from the three-centre shell model potential calculations [48]. So, from the experimental and theoretical studies, the neutron-rich Ni or/and Ca isotopes associated fragmentations are the most preferred ternary breakup.…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier fission studies [34,36], we have considered the arbitrary temperatures T = 1 and 2 MeV for all the fragmentations. This arbitrary temperature consideration is valid only for a particular fragmentation.…”
Section: Statistical Theorymentioning
confidence: 99%
See 2 more Smart Citations